2006
DOI: 10.1111/j.1365-2966.2006.10048.x
|View full text |Cite
|
Sign up to set email alerts
|

New planetary nebulae in the Galactic bulge region with l > 0 - II

Abstract: The presentation of new results from an [O iii] 5007‐Å survey in a search for planetary nebulae (PNe) in the Galactic bulge is continued. A total of 60 objects, including 19 new PNe, have been detected in the remaining 34 per cent of the survey area, while 41 objects are already known. Deep Hα+[N ii] CCD images as well as low‐resolution spectra have been acquired for these objects. Their spectral signatures suggest that the detected emission originates from photoionized nebulae. In addition, absolute line flux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
0
30
0
3
Order By: Relevance
“…Comparison of deep on-band and off-band CCD imaging (Beaulieu, Dopita & Freeman 1999;Boumis et al 2003Boumis et al , 2006 has found additional PN in the Galactic bulge. This technique has been used extremely successfully by Jacoby and co-workers for the discovery of numerous extragalactic PN (e.g.…”
Section: Image Comparison Techniquesmentioning
confidence: 99%
“…Comparison of deep on-band and off-band CCD imaging (Beaulieu, Dopita & Freeman 1999;Boumis et al 2003Boumis et al , 2006 has found additional PN in the Galactic bulge. This technique has been used extremely successfully by Jacoby and co-workers for the discovery of numerous extragalactic PN (e.g.…”
Section: Image Comparison Techniquesmentioning
confidence: 99%
“…An additional ∼450 PNe were then added from a large number of literature sources (e.g. Acker et al 1992Acker et al , 1996Kohoutek 1994Kohoutek , 2002Zanin et al 1997;Beaulieu et al 1999;Cappellaro et al 2001;Jacoby & Van de Steene 2004;Boumis et al 2003Boumis et al , 2006Górny 2006). As a further check we made use of updated coordinates provided by Kerber et al (2003) and SIMBAD to ensure no objects were missed.…”
Section: Planetary Nebulae Catalogue Constructionmentioning
confidence: 99%
“…Many surveys have been made in the past in order to discover new PNe (Boumis et al 2003 and references therein -Paper I, Boumis et al 2006-Paper II, Parker et al 2006 and references therein).…”
Section: Introductionmentioning
confidence: 97%